Організовані переселення в південні області Української РСР у 1955–1967 рр. - Жбанова, К. (Сiверянський лiтопис, 2015)
У статті розглянуто механізм державного регулювання трудових переселень з
УРСР в її південні області у 1955–1967 рр. Визначено основні напрямки та практичні
результати переселень. Проаналізовано функціонування системи пільг, якою користувалися переміщені родини, та визначено причини труднощів закріплення переселених
сімей на нових місцях проживання. Матеріал ґрунтується на архівних джерелах,
багатий фактичними даними, що дозволяє зрозуміти сутність процесу переміщень радянської доби. В статье рассмотрено механизм государственного регулирования трудовых переселений с УССР в ее южные области в 1955–1967 гг. Определены основные направления и практические результаты переселений. Проанализировано функционирование
системы льгот, которой пользовались перемещенные семьи, и определены причины
трудностей закрепления переселенных семей на новых местах проживания. Материал основывается на архивных источниках, богатый фактическими данными, что позволяет понять сущность процесса перемещений советской эпохи. The scientific study of the history of labor, employment, migration in search of work helps
to better understand the history of Ukraine as a whole.
This article is a study of labor migration in the period of the Main Directorate of organized
recruitment and relocation of workers of the Ukraine SSR. It is about attracting people to
work in rural areas in the southern regions of the country.
It has been analyzed the state migration policy and its economic and social consequences.
The processes of implementing the resettlement working population in the region are investigated.
The main directions and practical results migrations are determined. The system of
privileges for families that were resettlement are analyzed.
The material is based on archival sources, with rich factual data that allows us to understand
the essence of the process of resettlement working population in Soviet era.
The author comes to the conclusion that, the main source of the increase of labor in southern
regions of the Ukrainian SSR in 1955-1967 was planned relocation of families from other
regions of the republic, mainly western and central. Organized resettlements had had agricultural
character and were associated with the addition into state farms working population
and the creation of new resettlement villages in the southern regions of the republic. Organized
resettlements in 50-60th. XX century. have played a key role in recruiting manpower in Crimea,
Mykolaiv, Kherson regions that were devastated by war, famine and previous deportations.
However, in the regions which were left by settlers the government policy has led to spraying
the local population and ultimately had caused population losses.